PENGARUH PEMBERIAN LIMBAH TAHU DAN EM4 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CAISIM (Brassica juncea L.) - Carolina, Tya Anniza; Maryani, Yekti; Widata, Sri (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to determine the effect of the waste tofu and EM4 on the growth and yield chinese green mustard. The experiment was conducted in the field of Merapi Organic Farm, located in Balangan Wukirsari village, Cangkringan, Sleman Yogyakarta. The altitude is 500 meters above sea level with temperature of 23 0C - 29 0C and regosol soil type. This research was conducted in October through December 2016. The experiment was a factorial 4 x 2 and one control, arranged in a randomized complete block design. The treatment consists of two factors, the first factor is the concentration of waste tofu. The second factor is EM4 and without adding EM4. Each treatment was repeated three times. Observations included plant height, leaf number, fresh weight of canopy, fresh root weight, dry weight of canopy, root dry weight, dry weight of plant and yield per hectare. The result of analysis shows that there is no interaction between the two factors on growth and yield variables. Provision of waste tofu and EM4 showed no real effect on growth and crop yields